ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT GENERASI Z DALAM BUDIDAYA DOMBA GARUT - Cindy Nabila Noer Anhar; Kusmayadi, Tendy; Rohayati, Tati (Universitas Garut, 2025)
Breeder regeneration is very important to support sustainable livestock programs. This study aims to analyze the factors that influence generation Z's interest in Garut sheep farming. Generation Z's interest in Garut sheep farming can be influenced by various factors including preferences, heredity, family economy and culture. The research method uses a survey method. The population in this study were participants in the SKDG event at the Governor's Cup Open Contest in Pamidangan Arlamba Rancabango Garut Regency. The sampling technique used a purposive sampling technique, namely participants aged 13 to 31 years totaling 117 respondents with a questionnaire as a data collection instrument which was then processed using SPSS 25. The results of the study showed that simultaneously the variables of preferences, heredity, family economy and culture had a significant effect on generation Z's interest with an influence value of 54.9%. Partially, the variables of preference, descent and family economy have a significant effect, while culture does not affect the interests of Generation Z in cultivating Garut sheep. The influence of the variables of preference, descent and family economy on the interest of generation Z in cultivating Garut sheep was 28.2%, 19.6% and 35.3% respectively.